Excellent dementia care in hospitals : a guide to supporting people with dementia and their carers - James, Jo (Lead nurse); Knight, Jules; Cotton, Bethany; Freyne, Rita; Pettit, Josh; Gilby, Lucy (Bradford Dementia Group good practice guides., 2017)
Hospital workers are increasingly expected to have the knowledge and skills to care for people with dementia. This best-practice guide presents key information and strategies for working with people with dementia in hospitals to manage common issues. With a focus on person-centred care, this is an essential resource for healthcare staff.